Effects of Cement Dusts on Peak Expiratory Flow Rate (PEFR) in Female Cement Dust Exposed Construction Workers - Akter, Mst Merina; Sarka, Chandra Rani; Zahid, ATM Zoadur Rahim (Journal of Rangpur Medical College, 2023)
Background: Occupational and environmental lung diseases are the major problems of clinical medicine. The cement dust workers are constantly exposed to high amounts of visible ambient air particulate matter, mostly without any respiratory protective device. Therefore, the inhalation of dust over periods of time leads to impaired lung functions. Objectives: To observe the effects of cement dust exposure on PEFR in female cement dust workers. Methods: This cross-sectional study was conducted in the Department of Physiology, Rangpur Medical College, Rangpur from July 2016 to June 2017. A total of 60 female subjects aged 20–50 years were selected for the study. Among them, 30 were apparently healthy workers exposed to cement dust, and 30 apparently healthy height, weight & BMI-matched subjects not exposed to cement dust were selected as control from the surrounding community. Their pulmonary functions were studied by measuring PEFR. For statistical analysis, an unpaired ‘t’-test was performed by computer-based software SPSS-17.0 version for Windows. Results: The mean measured and mean percentage of the predicted value of PEFR was significantly (p_0.001) lower in cement dust-exposed female workers (CD- EFW) than the non-exposed female workers (CD-NEFW). Conclusion: From the result of this study, it can be concluded that cement dust (CD) may have harmful effects on some pulmonary functions. J Rang Med Col. September 2023; Vol. 8, No. 2: 25-28